Promoting equity with a multi-principle framework to allocate scarce ICU resources - White, Douglas (Journal of medical ethics, 2022)
We wholeheartedly agree with Schmidt and colleagues’ efforts to promote equity in intensive care unit (ICU) triage. We also take issue with their characterisation of the New Jersey (NJ) allocation framework for ICU beds and ventilators, which is modelled after the multi-principle allocation framework we developed early in the pandemic. They characterise it as a two-criterion allocation framework and claim—without evidence—that it will ‘compound disadvantage for black patients’. However, the NJ triage framework—like the model allocation policy we developed—actually contains four allocation criteria: the two criteria that the authors mentioned (chances for survival and near-term prognosis) and two criteria that they failed to mention which we included to promote equity: giving priority to frontline essential workers and giving priority to younger patients. These omissions are problematic both for reasons of factual accuracy and because the two criteria they failed to acknowledge would likely mitigate rather than exacerbate racial disparities during triage.